Mindfulness-based cognitive therapy may reduce thought suppression in previously suicidal participants: findings from a preliminary study. - Hepburn, SR; Crane, C; Barnhofer, T; Duggan, D; Fennell, M; Williams, J (2009)
OBJECTIVES: Thought suppression is a strategy aimed at mental control that may paradoxically increase the frequency of unwanted thoughts. This preliminary study examined effects of mindfulness-based cognitive therapy (MBCT) on thought suppression and depression in individuals with past depression and suicidality. METHODS: In a randomized controlled trial design, 68 participants were allocated to an MBCT group or a treatment-as-usual waitlist control. Measures of thought suppression and depression were taken pre- and post-treatment. RESULTS: MBCT did not reduce thought suppression as measured by the White Bear Suppression Inventory, but significantly reduced self-reported attempts to suppress in the previous week. CONCLUSIONS: Preliminary evidence suggests that MBCT for suicidality may reduce thought suppression, but differential effects on thought suppression measures warrant further studies.